Exploring deregulated signals involved in motor neuron-microglia cross-talk in ALS - Cunha, Maria Inês Fazendeiro (2014)
Part of the results discussed in this thesis was presented in the following meetings: Cunha MI, Cunha C, Vaz AR, Brites D. Studying microglial-motoneuron cross-talk in ALS pathology. 6th iMed.UL Postgraduate Students Meeting, Lisbon, July 2, 2014. [Abstract and Poster] Vaz AR. Motoneuron degeneration and glial reactivity in ALS: insights from cellular to animal models. Neuroscience Seminars at IMM 2012, Instituto de Medicina Molecular, Universidade de Lisboa, Lisbon, Portugal, June 9, 2014. [Oral Communication (by invitation)]